Geological, Tectonic Geochemical and Geochronological Properties of Travertine Occurrences Along the Strike-Slip Fault Systems: A Case From Southweatern Part of Sivrice (Elazig) - Colak Erol, Serap (Tmmob Jeoloji Muhendisleri Odasi, 2016)
The East Anatolian fault system (EAFS) of left lateral strike-slip is the second most important neotectonic structure of Turkey. The travertine occurrence is located on the Sivrice fault zone, which is one the significant zone of the EAFS and precipitated on a S to SW-facing slope, 20 km SW of the Sivrice town (Elazig) in accordance with the slope topography. The Maden Group of Middle Eocene age, on which the travertine occurrence took place, composed mostly of mudstones with volcanic intercalations, andesite, basalt and diabase dykes that cut them. The Puturge Metamorfics that play role as a basement rock are represented by calcschist and marble around their Sivrice exposures. Lithology of the Puturge Metamorfics and the fractured structure of the left lateral strike-slip Sivrice Fault Zone play an important role on the travertine formation. As the travertine exposures has been precipitated under appropriate conditions that formed by faults and bedrock in front of a fault along the left lateral strike-slip fault zone with normal component, they have been evaluated as 'fault-front travertines' depending on the morphological classification. The most abundant element concentrations of the travertine samples are: Ca: 378216-385220 ppm, Mg: 5428-8021 ppm, Sr: 2133-6046 ppm. The delta C-13 values range from +3,5 to +6,7 (parts per thousand PDB), while the delta O-18 values are between -8.1 and -9.6 (parts per thousand PDB). These geochemical signatures indicate that the travertines studied are of thermogene origin. Travertine precipitation began at least 30.86 +/- 0.49 ka ago with respect to today in the field based on the U-Th age data.
Keywords: Left lateral strike-slip fault; range-front travertine; The East Anatolian Fault System; U-Th dating